Dairy Cows’ Body Condition Score. Effects on reproduction, health and milk production. Use in farm management - OIKONOMOU (Γ. ΟΙΚΟΝΟΜΟΥ) G.; BAZDAGIANNI (Ζ. ΜΠΑΣΔΑΓΙΑΝΝΗ) Z.; VALERGAKIS (Γ. Ε. ΒΑΛΕΡΓΑΚΗΣ) G. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Body Condition Scoring (BCS) is an assessment of dairy cows’ subcutaneous fatty tissue that can provide useful information on their body energy reserves. It is a quick and easy to perform method that does not require special equipment and can be easily used at farm level. A body condition scoring method based on visual observation of specific body regions has been described. A 5 point scale (1 = emaciated, 5 = obese) is used. Low BCS and high BCS losses were found to have adverse effects on cows’ reproductive performance. Low or high BCS and high BCS losses were also found to have adverse effects on cows’ health, while they were also found to significantly affect milk production. Body condition score has medium-high heritability and significant genetic correlation with reproduction. Body condition score levels should be 3-3.25 at calving, not higher than 3.25 at drying off and at least 2.5 60-80 days post calving. Farmers and their consultants should try to achieve these goals through proper management. Body condition scoring can be performed at calving, 30 days post calving, at first artificial insemination, at mid-lactation and at drying off.